Mechanism of Tripterygium wilfordii Hook.F.- Trichosanthes kirilowii Maxim decoction in treatment of diabetic kidney disease based on network pharmacology and molecular docking - Lu, Lingfei; Peng, Jinting; Wan, Peijun; Peng, Hongcheng; Lu, Jiandong; Xiong, Guoliang (Frontiers in Pharmacology, 2022)
Background: Diabetic kidney disease (DKD) is the most common cause of end-stage renal disease. The effective treatment of DKD would rely on the incorporation of a multi-disciplinary. Studies have shown that Tripterygium wilfordii Hook.F. and Trichosanthes kirilowii Maxim have remarkable curative effects in treating DKD, but their combination mechanism has not been fully elucidated. Methods: We explored the mechanism of action of Tripterygium wilfordii Hook.F.-Trichosanthes kirilowii Maxim decoction (Leigongteng-Tianhuanfen decoction, LTD) in the treatment of DKD by network pharmacology and molecular docking. The main active components and action targets of LTD were collected from Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) database. The speculative targets of DKD were obtained from GeneCards, DisGeNET, and Online Mendelian Inheritance in Man (OMIM) databases. Then, an herb-component-target network was constructed based on the above analyses. The biological function of targets was subsequently investigated, and a protein-protein interaction (PPI) network was constructed to identify hub targets of DKD. The GO function enrichment analysis and KEGG pathway enrichment analysis were performed by RStudio. Finally, molecular docking was performed by AutoDock Vina and PyMOL software to explore the interaction between compounds and targets. Results：A total of 31 active components of LTD were screened out, and 196 targets were identified based on the TCMSP database. A total of 3,481 DKD related targets were obtained based on GeneCards, DisGeNET, and OMIM databases. GO function enrichment analysis included 2143, 50, and 167 GO terms for biological processes, cell components, and molecular functions, respectively.The involvement signaling pathway of LTD in the treatment of DKD included AGE-RAGE signaling pathway in diabetic complications, IL-17 signaling pathway, insulin resistance, TNF signaling pathway, etc. Molecular docking results showed that kaempferol, triptolide, and schottenol had a strong binding ability to PTGS2 and RELA. Furthermore, the in vitro experiments confirmed that LTD effectively decreased the expression of PTGS2, NF-κB, JNK, and AKT in the HG-induced DKD model. Conclusion: The findings of this study revealed that the therapeutic efficacy of LTD on DKD might be achieved by improving insulin resistance, inflammation, and oxidative stress, which provides ideas and supplies the potential therapeutic targets for DKD.